The Effect of Government Spending on Education, Health, Unemployment, and Economic Growth on the Human Development Index in Lombok Timur Regency 2013-2022 - Dinwan Yozi Saputra; Himawan Sutanto; Ida Ayu Putri Suprapti (Tinta Emas Institute, 2024)
The Human Development Index (HDI) is an indicator used to measure the level of development of an area, especially East Lombok Regency in West Nusa Tenggara Province. This research aims to analyze the influence of government spending on education and health, unemployment and economic growth, whether they simultaneously influence the Human Development Index in Lombok Timur district in 2013-2022. This research is a type of descriptive research with a quantitative approach and using statistical methods. Statistical analysis aims to test the hypothesis before the data is processed, the researcher changed the annual data above into quarterly data using Eviews 10. The Influence of Government Expenditures in the Education and Health Sectors, Unemployment and Economic Growth on the Human Development Index in East Lombok Regency in 2013 -2022 based on the results of research data that has been tested, it is concluded that the four independent variables have an effect simultaneously or together on the dependent variable, this is expressed by a probability value (F statistic) which is 0.000, which is smaller than the allowable error of 0.05. Meanwhile, partially the variables Expenditure on Education and Economic Growth have a positive effect, while the variables Government Expenditure on Health and Unemployment have a negative effect on the Human Development Index in Lombok Timur Regency in 2013-2022.